The nasal carrier rate of Staphylococcus aureus and methicillın- resistant Staphylococcus aureus among Turgut Özal Medical Center staff (Annals of Medical Research, 2021)
None
Keywords: Staphylococcus aureus, nasal carriage, hospital staff